Consequences of Diversity for Social Cohesion and Prejudice: The Missing Dimension of Intergroup Contact. (June 2015) - Hewstone, Miles; Hunter, Andrea G.; Stewart, Abigail J.
<x xml:space="preserve">Abstract</x> A controversial claim that diversity has negative consequences for trust and other outcomes spawned a contentious debate in sociology and political science, but was hardly noted in social psychology. I summarize the debate, and argue that the efficacy of direct, face‐to‐face intergroup contact as a means of reducing prejudice is a stark omission, as I illustrate with evidence of the association between diversity, on the one hand, and trust, prejudice, and social capital on the other. I also consider two other contributions of contact theory to this issue, namely that contact with members of one group has an impact on attitudes toward members of other groups; and that contact should be studied via social networks. Despite the importance I attach to contact, I note two "enemies of contact, " resegregation in ostensibly desegregated settings, and negatively valenced contact. Finally, I point to the kind of research we should do, in order to increase the impact of our work on the public policy debate on this issue.